The dynamic of secondary hemorrhagic progression of contusion in traumatic brain injury - M. B. Vyval; M. E. Polishchuk; Y. M. Perekopaiko (Kazimierz Wielki University, 2017)
Vyval M. B., Polishchuk M. E., Perekopaiko Y. M. The dynamic of secondary hemorrhagic progression of contusion in traumatic brain injury. Journal of Education, Health and Sport. 2017;7(1): 369-376. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.292929 http://ojs.ukw.edu.pl/index.php/johs/article/view/4271       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2017; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.01.2017. Revised 16.01.2017. Accepted: 24.01.2017.   УДК 616.831-001.3-005.1   The dynamic of secondary hemorrhagic progression of contusion in traumatic brain injury   M. B. Vyval, M. E. Polishchuk, Y. M. Perekopaiko   Department of Neurosurgery, National Medical Academy of Postgraduate Education named after P.L. Shupik, Ministry of Health of Ukraine, Kyiv, Ukraine Traumatology Department, Ternopil City Municipal Hospital of Emergency medicine , Ternopil, Ukraine   Abstract Introduction. Secondary posttraumatic changes in the brain often determine the clinical flow during traumatic brain injury (TBI). Prevention and early detection of secondary hemorrhagic progression (SHP) is very important  for determination of the treatment strategy in patients with brain contusion. We studied the dynamic of brain contusion and its impact on the clinical course of brain injury. We found that the secondary hemorrhagic progression of contusion occurs in 43% and can be detected at the place of primary brain damage, and far away from it, and often can be seen in patients with a subdural hematoma. The larger contusion has the greater probability of progression and needs for surgical decompression. Progression is associated with the significant risk of clinical deterioration and mortality. Conclusions. Treatment tactics depends on severity of volumetric effect on the surrounding brain structures and manifestations of herniation syndrome. Key words: traumatic brain injury, brain contusion, secondary hemorrhagic progression of contusion.